Report on the current food and domestic demand situation in the countries of the Lesser Antilles as part of the study on the competitiveness of the agriculture sector in the Lesser Antilles - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
53 páginas